2021
DOI: 10.3390/ani11072000
|View full text |Cite
|
Sign up to set email alerts
|

Use of Hydrolyzed Chinese Gallnut Tannic Acid in Weaned Piglets as an Alternative to Zinc Oxide: Overview on the Gut Microbiota

Abstract: The effects of dietary hydrolyzed Chinese gallnut tannic acid(GCT) as a replacement for ZnO were investigated on weaned piglets. A total of 72 weaned piglets at 31 ± 1 day (six replicate pens per treatment with six piglets per pen) were selected and divided randomly into two groups: a control group, with a basal diet of + 1600 mg/kg ZnO; and a treated group, with a basal diet of + 1899.5 mg/kg GCT. Data analysis showed that the significance of average daily gain and average daily feed intake between the two gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 26 publications
1
6
1
Order By: Relevance
“…These outcomes suggested that 3.0 kg/t TA may be a good alternative for ZnO in weaned piglets. A previous study has shown that dietary supplementation of hydrolyzed TA at 1899.5 mg/kg could be an alternative for ZnO in piglets [13], while the dose of TA is inconsistent with our results. This may take into account that hydrolyzed TA reduces the combination between TA and digestive enzymes, thereby enhancing TA bioactivities [11].…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…These outcomes suggested that 3.0 kg/t TA may be a good alternative for ZnO in weaned piglets. A previous study has shown that dietary supplementation of hydrolyzed TA at 1899.5 mg/kg could be an alternative for ZnO in piglets [13], while the dose of TA is inconsistent with our results. This may take into account that hydrolyzed TA reduces the combination between TA and digestive enzymes, thereby enhancing TA bioactivities [11].…”
Section: Discussioncontrasting
confidence: 99%
“…TA have shown to linearly reduce the growth performance of weanling pigs [29,30]. However, many recent studies have observed that the dietary TA supplementation at an appropriate dose had no effect on growth performance and nutrient digestibility in piglets [12][13][14][15]. In agreement with this, the current study shows that dietary supplementation of 1.5 or 3.0 kg/t gallnut TA had no adverse effect on the growth performance in weanling piglets.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This can be achieved by measuring the molecules that contribute to this interaction, especially the metabolites formed by the microbiota that are available for uptake by the host. Gut microbes play a key role in animal health, including digesting food, metabolism, regulating immunity, and defending against invading pathogens (56)(57)(58). The composition of different microbial communities in the digestive tract of animals is different, and the diversity and density of microbial communities increase gradually from the stomach to the hindgut (59).…”
Section: Discussionmentioning
confidence: 99%
“…At the nursery stage, which is from the weaning stage to 10 weeks and body weight of less than 30 kg [ 38 ], energy is mainly used to eliminate negative effects caused by weaning stress and to complete the immune system. Thus, the growth of the nursery pigs is slow [ 39 , 40 ]. Therefore, we continued to monitor the growth for an extra month.…”
Section: Discussionmentioning
confidence: 99%